2010
DOI: 10.1158/1535-7163.mct-10-0205
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Differentially Targeting Dual Virotherapy for Human Solid Cancer

Abstract: Multimodal approaches combining drugs that differentially function is the most popular regimen for treating human cancer. Understanding the molecular mechanisms underlying the synergistic, potentiative, and antagonistic effects of drug combinations could facilitate the discovery of novel efficacious combinations. We previously showed that telomerase-specific replication-competent adenovirus (Telomelysin,, in which the human telomerase reverse transcriptase promoter controls the adenoviral E1 gene expression, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We recently reported that combination therapy with OBP-301 and Adp53 resulted in a more profound antitumor effect than monotherapy with either OBP-301 or Ad-p53 (25). Moreover, we generated armed OBP-301 expressing the wildtype p53 tumor suppressor gene (OBP-702) and showed that OBP-702 suppressed the viability of various types of epithelial malignant cells more efficiently than did OBP-301 (26).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that combination therapy with OBP-301 and Adp53 resulted in a more profound antitumor effect than monotherapy with either OBP-301 or Ad-p53 (25). Moreover, we generated armed OBP-301 expressing the wildtype p53 tumor suppressor gene (OBP-702) and showed that OBP-702 suppressed the viability of various types of epithelial malignant cells more efficiently than did OBP-301 (26).…”
Section: Introductionmentioning
confidence: 99%
“…Upon infection, E1A and E1B are expressed and induce viral replication and cellular lysis in TERT promoter active tumor cells, while sparing TERT promoter inactive benign cells [ 160 ]. In vitro , the oncolytic virus OBP-301 (telomelysin) has been shown to selectively lyse lung cancer cells [ 161 ], kill CD133+ human gastric cancer stem-like cells [ 162 ], and inhibit lung tumor xenografts treated with direct intratumoral injection [ 163 ]. In phase I testing, OBP-301 was well tolerated at three different dose levels with no serious adverse events [ 136 ].…”
Section: Telomere and Telomerase Therapeuticsmentioning
confidence: 99%
“…For example, AD5CMV-p53 is an adenoviral vector encoding p53 that was shown to replenish p53 in p53 deficient tumor cells. This approach inhibited lung cancer cell growth both in vitro and in vivo [141]. Clinical phase I and II trials have subsequently demonstrated that this agent is both safe and effective against esophageal squamous cell carcinoma [142, 143].…”
Section: Fak Inhibitorsmentioning
confidence: 99%